2022
DOI: 10.1093/ageing/afac266
|View full text |Cite
|
Sign up to set email alerts
|

Dementia and hearing-aid use: a two-way street

Abstract: Objectives Hearing-aid use may reduce risk of dementia, but cognitive impairment makes use more challenging. An observed association between reduced hearing-aid use and incident dementia could reflect either or both of these causal paths. The objective was to examine the effects of each path while minimising contamination between paths. Methods Health records data from 380,794 Veterans who obtained hearing aids from the US Ve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 31 publications
0
15
0
2
Order By: Relevance
“…Clinically and ethically, hearing devices and hearing care processes must be accessible and usable for all, regardless of cognitive status. Naylor et al reported that patients over 60 years of age with a pre‐existing dementia diagnosis prior to HA fitting had 54% reduced odds of persistent HA use compared to those who remained free of MCI and dementia throughout the study time window 28 . The identification of MCI due to AD, and thus the preclinical stage of AD, is becoming increasingly important to clarify the direction of early intervention and prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically and ethically, hearing devices and hearing care processes must be accessible and usable for all, regardless of cognitive status. Naylor et al reported that patients over 60 years of age with a pre‐existing dementia diagnosis prior to HA fitting had 54% reduced odds of persistent HA use compared to those who remained free of MCI and dementia throughout the study time window 28 . The identification of MCI due to AD, and thus the preclinical stage of AD, is becoming increasingly important to clarify the direction of early intervention and prevention.…”
Section: Discussionmentioning
confidence: 99%
“…It remains an open question as to whether earlier intervention for hearing loss could help to prevent or delay cognitive impairment. There are encouraging signs in the literature ( 63 ), but there is a lack of prospective research to demonstrate such benefits. In any case, in order to be able to undertake such studies requires early identification of hearing problems.…”
Section: Discussionmentioning
confidence: 99%
“…Bereits subklinische Hörstörungen führen zu einer Verschlechterung der Kognition. Zudem konnte auch gezeigt werden, dass kognitive Störungen zu einer reduzierten Inanspruchnahme von Hörhilfen führen [21].…”
Section: Schwerhörigkeitunclassified